Meningkatkan Hasil Belajar IPS Siswa Menggunakan Model Pembelajaran Somatik, Auditori, Visual, Intelektual (SAVI) di Kelas V SDN Menteng Atas 14 - Dita Amelia Asshiba; Mahmud Yunus; Dina Rahmi Darman (Mataram University, 2026)
This study aims to improve the learning outcomes of social studies students of class V-B SDN Menteng Atas 14 through the application of the Somatic, Auditory, Visual, and Intellectual (SAVI) learning model. This study uses the Classroom Action Research (CAR) method. Data were collected through observation sheets, learning outcome tests, field notes, and documentation. Student learning outcomes were measured based on the percentage of students who achieved the Learning Objective Achievement Criteria with a minimum score of ≥75, while the research success indicator was determined if at least 85% of students achieved ≥75. The results showed an increase in teacher activity, student activity, and student learning outcomes from cycle I to cycle II. In cycle I, teacher activity reached 85.70% and student activity reached 76.20%, while the percentage of student learning outcome completion was 60.87%, so it had not reached the established success indicator. After the implementation of cycle II, teacher activity increased to 100%, student activity to 95.20%, and the percentage of student learning outcome completion increased to 91.30%, so it had exceeded the research success indicator. The implementation of the SAVI learning model makes the learning process more interactive and meaningful, making it easier for students to understand the material being studied. Therefore, the SAVI learning model is effective in improving elementary school students' social studies learning outcomes.